Coaching shared mental models in soccer: A longitudinal case study - Gershgoren, L.; Filho, E. M.; Tenenbaum, G.; Schinke, R. J. (Journal of Clinical Sport Psychology, 2013)
This study was aimed at capturing the components comprising shared mental models (SMM) and the training methods used to address SMM in one athletic program context. To meet this aim. two soccer coaches from the same collegiate program were interviewed and observed extensively during practices and games throughout the 2009-2010 season. In addition, documents (e.g. players' positioning on free kicks sheet) from the soccer program were reviewed. The data were analyzed inductively through a thematic analysis to develop models that operationalize SMM through its components, and training. Game intelligence and game philosophy were the two main operational themes defining SMM. Moreover, four themes emerged for SMM training: (a) the setting, (b) compensatory communication, (c) reinforcement, and (d) instruction. SMM was embedded within a more comprehensive conceptual framework of team chemistry, including emotional, social, and cognitive dimensions. Implications of these conceptual frameworks are considered for sport psychologists and coaches.